Teaching science - Liversidge, Tony.; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2009)
Reflective practice is at the heart of effective teaching, and this title helps you develop into a reflective teacher of science.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Science -- Study and teaching (Secondary); Reflective teaching; Electronic books